Force modulated conductance of artificial coiled‐coil protein monolayers1. Issue 1 (19th January 2013) - Atanassov, Alexander; Hendler, Ziv; Berkovich, Inbal; Ashkenasy, Gonen; Ashkenasy, Nurit; Maran, Flavio; Toniolo, Claudio
Abstract Studies of charge transport through proteins bridged between two electrodes have been the subject of intense research in recent years. However, the complex structure of proteins makes it difficult to elucidate transport mechanisms, and the use of simple peptide oligomers may be an over simplified model of the proteins. To bridge this structural gap, we present here studies of charge transport through artificial parallel coiled‐coil proteins conducted in dry environment. Protein monolayers uniaxially oriented at an angle of ∼ 30° with respect to the surface normal were prepared. Current voltage measurements, obtained using conductive‐probe atomic force microscopy, revealed the mechano‐electronic behavior of the protein films. It was found that the low voltage conductance of the protein monolayer increases linearly with applied force, mainly due to increase in the tip contact area. Negligible compression of the films for loads below 26 nN allowed estimating a tunneling attenuation factor, β0, of 0.5–0.6 Å−1, which is akin to charge transfer by tunneling mechanism, despite the comparably large charge transport distance. These studies show that mechano‐electronic behavior of proteins can shed light on their complex charge transport mechanisms, and on how these mechanisms depend on the detailed structure of the proteins. Such studies may provide insightful information on charge transfer in biological systems. © 2012 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 93–99, 2013.